Application of Disulfiram and its Metabolites in Treatment of Inflammatory Disorders - Guo, Wenyi; Chen, Shihong; Li, Chengqing; Xu, Jianwei; Wang, Lei (Frontiers in Pharmacology, 2022)
Disulfiram has been used clinically for decades as an anti-alcoholic drug. Recently, several studies demonstrate the anti-inflammatory effects of disulfiram, which can alleviate the progression of inflammation in vivo and in vitro. In the current study, we summarize the anti-inflammatory mechanisms of disulfiram, including inhibition of pyroptosis by either covalently modifying gasdermin D or inactivating nod-like receptor protein 3 inflammasome, dual effects of intracellular reactive oxygen species production, and inhibition of angiogenesis. Furthermore, we review the potential application of disulfiram in treatment of inflammatory disorders, such as inflammatory bowel disease, inflammatory injury of kidney and liver, type 2 diabetes mellitus, sepsis, uveitis, and osteoarthritis.